Structure and method for improving anti-ESD capability of UVC LED device

By setting a multi-layer structure in the n-type semiconductor layer of the UVC LED device, adjusting the Al component content and n-type doping concentration, the problem of poor anti-static ability of the UVC LED device is solved, and the effect of improving ESD performance and extending service life is achieved.

CN119653940APending Publication Date: 2025-03-18SUZHOU LEKIN SEMICON CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411689131.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Due to poor material quality and small p-type layer thickness, UVC LED devices have poor antistatic ability, which affects the reliability and service life of the device.

Method used

By providing a multi-layer structure in the n-type semiconductor layer of the UVC LED device, specifically including the first layer, the second layer, the third layer and the fourth layer, the Al component content and n-type doping concentration of each layer are arranged in a specific gradient to improve the buffering and deceleration of electrons and the expansion ability of current.

Benefits of technology

This method effectively improves the antistatic ability of UVC LED devices, improves ESD performance, and reduces the operating voltage and resistance value of the device, thereby extending the service life of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119653940A_ABST
    Figure CN119653940A_ABST
Patent Text Reader

Abstract

The invention discloses a structure and method for improving the ESD resistance of a UVC LED device. The UVC epitaxial structure comprises an n-type semiconductor layer, an active layer and a p-type semiconductor layer, the n-type semiconductor layer comprises a first layer, a second layer and a third layer which are sequentially stacked in a specified direction, the first layer has a first Al component content, the second layer has a second Al component content, and the third layer has a third Al component content; the first layer at least comprises a first n-type doping concentration, the second layer at least comprises a second doping concentration, and the second layer at least comprises a third doping concentration; the content of the first Al component is larger than the content of the second Al component, the content of the third Al component is larger than the content of the first n-type doping concentration, the first n-type doping concentration is smaller than the second n-type doping concentration, the third n-type doping concentration is smaller than the third n-type doping concentration, and the first n-type doping concentration is low doping concentration or unintentional doping. According to the invention, from the fourth layer to the first layer in the n-type semiconductor layer, the content of the Al component corresponding to each layer is reduced first and then increased, the doping relation of each layer is controlled, and the ESD can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention particularly relates to a structure and method for improving the ESD resistance of a UVC LED device, and belongs to the field of semiconductor technology. Background Art

[0002] Because UVC LED devices use AlGaN materials with a high Al content, the material quality is worse than that of blue-green light LEDs, and the thickness of the p-type layer is only 60-90 nm. This leads to poor reliability of UVC LED devices, especially poor anti-static ability. This requires adding Zener tubes in parallel when packaging UVC LED devices to improve ESD and prevent the device from being broken down by static electricity, which greatly affects the service life of the device.

[0003] Therefore, it is necessary to develop a device that improves the lateral current expansion capability of UVC LED devices, thereby improving ESD devices. Summary of the invention

[0004] The main purpose of the present invention is to provide a structure and method for improving the ESD resistance of UVC LED devices, thereby overcoming the deficiencies in the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: A first aspect of an embodiment of the present invention provides a UVC epitaxial structure, comprising: an n-type semiconductor layer, an active layer and a p-type semiconductor layer stacked in sequence, wherein the n-type semiconductor layer, the active layer and the p-type semiconductor layer are made of AlGaN, and the n-type semiconductor layer comprises a first layer, a second layer and a third layer stacked in sequence along a specified direction, wherein the first layer has a first Al component content, the second layer has a second Al component content, and the third layer has a third Al component content; the first layer contains at least a first n-type doping concentration, the second layer contains at least a second doping concentration, and the third layer contains at least a third doping concentration; the first Al component content is greater than the second Al component content and the third Al component content, the first n-type doping concentration is less than the second n-type doping concentration and the third n-type doping concentration, and the first n-type doping concentration is a low doping concentration or unintentional doping; the specified direction is a direction from the active layer to the n-type semiconductor layer.

[0006] Furthermore, the first Al component content>the third Al component content>the second Al component content.

[0007] Furthermore, the first Al component content is 55%-65%, the first n-type doping concentration is low doping or unintentional doping, the low doping concentration is 1E17-5E17, and the unintentional doping concentration is <1E17.

[0008] Furthermore, the first n-type doping concentration is less than the third n-type doping concentration and less than the second n-type doping concentration.

[0009] Furthermore, the second Al component content is 40%-55%, and the second n-type doping concentration is 2E18-5E19.

[0010] Furthermore, the third Al component content is 50%-60%, and the third n-type doping concentration is 2E18-5E19.

[0011] Further, the thickness of the first layer is 80 nm-500 nm, and / or the thickness of the second layer is 80 nm-500 nm, and / or the thickness of the third layer is 400 nm-2 μm.

[0012] In a more specific embodiment, the n-type semiconductor layer also includes a fourth layer, which is stacked on the third layer along the specified direction, the fourth layer has a fourth Al component content, the fourth layer at least contains a fourth n-type doping concentration, the fourth Al component content is greater than or less than the first Al component content, and the fourth n-type doping concentration is greater than the first n-type doping concentration.

[0013] Furthermore, the fourth Al component content is greater than the first Al component content, the fourth n-type doping concentration is 2E18-5E19, and the fourth Al component content is 60%-80%.

[0014] A second aspect of an embodiment of the present invention provides a method for preparing a UVC epitaxial structure, comprising: forming the UVC epitaxial structure on a buffer layer, wherein the n-type semiconductor layer is stacked on the buffer layer, and the material of the buffer layer is AlN-based.

[0015] A third aspect of an embodiment of the present invention provides a semiconductor device, which includes an epitaxial structure and a first electrode and a second electrode matching the epitaxial structure, wherein the epitaxial structure is the UVC epitaxial structure.

[0016] Compared with the prior art, the advantages of the present invention include: From the fourth layer to the first layer of the n-type semiconductor layer in the present invention, the Al component content of each layer first decreases and then increases, which can effectively buffer and slow down the electrons, is also beneficial to improve droop and ESD, and can also reduce the electron buffer; The n-type doping concentration in the second layer of the n-type semiconductor in the present invention is increased, and the first layer is unintentionally doped or has a very low n-type doping concentration, which can achieve both a low device operating voltage and better current expansion, thereby improving ESD; The UVC LED device obtained by the present invention is simple to realize in terms of process, and while ensuring the quality of each layer, the electrical characteristics and life of the original device are not damaged, and the overall structural performance and life of the device are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a structural schematic diagram of a UVC epitaxial structure provided in a typical implementation case of the present invention; Figure 2 It is a schematic diagram of the energy band of a partial structure of a UVC epitaxial structure provided in a typical implementation case of the present invention; Figure 3 Schematic diagram of energy band distribution and SiH4 flow distribution of n-type semiconductor layer in Example 1 of the present invention; Figure 4 Schematic diagram of energy band distribution and SiH4 flow distribution of n-type semiconductor layer in Example 2 of the present invention; Figure 5 Schematic diagram of energy band distribution and SiH4 flow distribution of n-type semiconductor layer in Example 3 of the present invention; Figure 6 Schematic diagram of energy band distribution and SiH4 flow distribution of the n-type semiconductor layer in Comparative Example 1 of the present invention; Figure 7 Schematic diagram of energy band distribution and SiH4 flow distribution of n-type semiconductor layer in Comparative Example 2 of the present invention; Figure 8 It is a schematic diagram of the energy band distribution and SiH4 flow distribution of the n-type semiconductor layer in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0018] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0019] Terminology explanation: ESD: When the human body comes into contact with charged objects such as electronic devices, static discharge will occur. This phenomenon is called "ESD: Electro-Static Discharge". The ESD generated by the human body is a high voltage of several thousand volts. This high voltage pulse invades the inside of the electronic device being touched, causing the device to break down and fail.

[0020] The technical solution, its implementation process and principles, etc. will be further explained below in conjunction with the accompanying drawings and specific implementation cases. Unless otherwise specified, the semiconductor epitaxial growth process and the antistatic test of the device used in the embodiments of the present invention are equipment and testing methods that are known in the art and are not specifically limited here.

[0021] In a more specific implementation, see Figure 1 , Figure 2 A UVC epitaxial structure includes a substrate 100, a buffer layer 110, an n-type semiconductor layer 120, an active layer 130 and a p-type semiconductor layer 140 which are stacked in sequence.

[0022] Specifically, the material of the substrate 100 may be sapphire, silicon carbide or gallium nitride, etc. The material of the buffer layer 110 may be AlN, and the surface portion of the buffer layer 110 close to the n-type semiconductor layer 120 is a transition layer 111 with a gradually decreasing Al component content, and the transition layer may be a multi-layer gradient structure or a superlattice structure AlGaN / AlGaN with a decreasing Al content; the transition layer is an undoped layer.

[0023] Specifically, the material of the n-type semiconductor layer 120 can be AlGaN, and the n-type semiconductor layer 120 is a multi-layer structure, having a first layer 124, which is closest to the active layer, the first layer 124 has a first Al component content, and in a first direction from the quantum well to the first layer 124, a second layer 123 is arranged below the first layer 124, and the second layer 123 has a second Al component content; a third layer is arranged below the second layer, and the third layer has a third Al component content, and a fourth layer is arranged below the third layer, and the fourth layer has a fourth Al component content; further, according to process requirements, a transition can be made directly from the fourth layer to the third layer; in a direction opposite to the first direction, from the fourth layer 121 to the second layer 123, the Al component content gradually decreases; the fourth layer 121 is the layer closest to the buffer layer 110.

[0024] Specifically, the first Al component content of the first layer 124 is 55%-65%, and the high Al content is beneficial to electron buffering and current expansion. The second Al component content of the second layer 123 is 45%-55%, and the second layer serves as an electrode contact layer, thereby improving the ohmic contact performance. The third Al component content of the third layer 122 is 50%-60%, and the fourth Al component content of the fourth layer 121 is 60%-80%; the Al component content of the first layer is greater than the Al component content of the second layer and the Al component content of the third layer, thereby improving the current expansion performance and improving ESD, the second Al component content is less than or equal to the third Al component content, and the second Al component and the third Al component content are less than the fourth Al component content; the first Al component content is less than or equal to or greater than the fourth Al component content, but is not limited to this. Preferably, in order to improve the quality of the stacking crystal, the first Al component content is less than the fourth Al component content.

[0025] Specifically, SiH4 is used to provide doping for AlGaN to obtain an n-type doped semiconductor layer (n-AlGaN), so that each layer obtains a Si doping concentration with a corresponding trend; the first layer 124 includes a first n-type doping concentration, the second layer 122 includes a second n-type doping concentration, the third layer 123 includes a third n-type doping concentration, and the fourth layer 121 includes a fourth n-type doping concentration; the first n-type doping concentration is less than the second n-type doping concentration, the third n-type doping concentration, and the fourth n-type doping concentration; the flow rate of providing SiH4 to the first layer is a low flow rate or no SiH4 is provided, that is, the first n-type doping concentration is low doping or unintentional doping. When the first n-type doping concentration is low doping, its doping concentration is 1E17-5E17atoms / cm 3 When SiH4 is not provided, the first n-type doping concentration is unintentional doping, and the doping concentration is <1E17atoms / cm 3 The second layer 123, the third layer 122, and the fourth layer 121 provide a relatively higher SiH4 flow rate than the first layer, and the second n-type doping concentration, the third n-type doping concentration, and the fourth n-type doping concentration are 2E18-5E19atoms / cm 3 ; Further, the second n-type doping concentration is higher than the third n-type doping concentration to reduce the operating voltage; further, the fourth n-type doping concentration is greater than or less than the second n-type doping concentration, and more preferably, the fourth n-type dopant concentration is greater than the second n-type doping concentration and the third n-type doping concentration, which is more conducive to electron migration, but is not limited to this.

[0026] Specifically, the active layer 130 is composed of a plurality of Al x Ga 1-x N quantum barrier layer 132 and Al y Ga 1-y The N quantum well layer 131 is grown alternately, and multiple alternating quantum barrier layers and quantum well layers are implemented in 1-7 cycles; the p-type semiconductor layer 140 can be a p-AlGaN or p-GaN layer, and the P-type layer includes an electron blocking layer AlGaN, a hole injection layer Al(In)GaN and a contact layer AlGN and / or GaN. In order to improve contact performance and avoid light absorption, the contact layer can have a composition of 10-30nmAlGaN or 1-10nmGaN.

[0027] Specifically, the UVC LED is grown on high Al component AlGaN or high Al component AlN. The fourth layer 121 can transition from high Al component to low Al component, reduce the relaxation stress caused by the lattice mismatch and surface roughness of the crystal stacking, obtain a smooth surface, and lay a good foundation for subsequent crystal stacking. The Al component content in the fourth layer 121 is generally 60-80%, preferably 70%.

[0028] Specifically, the third layer 122 serves as the main current expansion layer, and the Al component content is 50-60%. At this time, it will not absorb the deep ultraviolet light with a wavelength of 270nm-280nm emitted by the MQW layer, and can also achieve higher conductivity, which is convenient for the n-electrode to expand the current, thereby reducing the device voltage.

[0029] Specifically, the second layer 123 is used as the N-electrode contact layer, and its component control is lower than that of the fourth layer and / or the third layer. The low Al component content is more conducive to achieving n-side ohmic contact. Further, when the Al component content corresponding to the second layer 123 is about 5%-10% lower than the Al component content in the third layer 122, the best balance can be achieved in avoiding light absorption and obtaining the best ohmic contact, and the overall performance of the best device electrical characteristics and luminous efficiency can be obtained. The Si doping concentration of the second layer 123 in the present invention is relatively high, forming a good n-type ohmic contact and reducing the device operating voltage; Specifically, the second layer 123 serves as the N-electrode contact layer, and the first layer 124 covers the second layer 123. After the current expands laterally in the second layer 123, due to the high Al component content in the first layer 124 and no Si doping or very low doping concentration, the resistance of the first layer 124 is relatively large, allowing the current to better expand laterally in the second layer 123, thereby improving the ESD resistance. The Al component content in the first layer 124 is generally 55%-65%. If the component is too high, it will affect the lattice adaptation between the N-type AlGaN and the active layer, causing lattice defects and affecting the light extraction efficiency. If the Al component is too low, it will affect the current expansion and reduce the ESD performance.

[0030] Specifically, the thickness of the first layer 124 is 80 nm-500 nm, preferably 100 nm-300 nm. If the thickness of the first layer 124 is too thin, the current expansion effect will be poor, and if the thickness of the first layer 124 is too thick, the crystal quality will be degraded, which will affect the device performance. The increase in the n-type doping concentration of the second layer 123 can compensate for the increase in resistance of the first layer 124 due to the improvement of ESD undoping, and reduce the working voltage that the device can achieve; the low doping or undoping of the first layer 124, the high doping of the second layer, and the control of the Al group components of each layer, the coordinated effect of various factors can improve the ESD performance of the device and ensure the comprehensive performance of the device, reaching the high quality level of industrial application.

[0031] In the present invention, the Al component and doping of each layer in the n-type semiconductor layer are optimized, and the Al component content corresponding to each layer is first reduced and then increased, which can effectively buffer and slow down the electrons, greatly helps to improve ESD, reduce droop, reduce the resistance value of the entire device, and improve the device life.

[0032] The technical solution, its implementation process and principle will be further explained below in conjunction with specific embodiments.

[0033] Example 1 A UVC epitaxial structure includes a substrate 100, a buffer layer 110, an n-type semiconductor layer 120, an active layer 130 and a p-type semiconductor layer 140 which are stacked in sequence.

[0034] In this embodiment, the substrate 100 is a sapphire substrate, the buffer layer 110 is an AlN buffer layer, the thickness of the AlN buffer layer is 2.5 μm, the thickness of the Al composition gradient layer 111 of the AlN buffer layer close to the n-type semiconductor layer 120 is 500 nm, and the active layer 130 includes 5 periods of Al 0.65 Ga 0.35 N quantum barrier layer 132 and Al 0.45 Ga 0.55 The thickness of the N quantum well layer 131 and the AlGaN quantum barrier layer 132 is 10 nm. 0.45 Ga 0.55 The thickness of the N quantum well layer 131 is 1.5 nm. The p-type semiconductor layer 140 is a p-AlGaN layer. The thickness of the p-type semiconductor layer 140 is 60 nm.

[0035] The n-type semiconductor layer 120 in this embodiment includes a first layer 124, a second layer 123, a third layer 122, and a fourth layer 121 which are sequentially stacked between the buffer layer 110 and the active layer 130. The first layer 124 is a layer closest to the active layer 130, and the fourth layer 121 is a layer closest to the buffer layer 110. The second layer 123, the third layer 122, and the fourth layer 121 are all Si-doped with SiH4 to form a Si-doped n-AlGaN layer. The first layer 124 is an unintentionally doped u-AlGaN layer. The thickness of the first layer 124 is 250 nm, and the first Al component content in the first layer 124 is 60%. The thickness of the second layer 123 is 400 nm, and the second Al component content in the second layer 123 is 45%. The doping concentration of Si is 3E19. The thickness of the third layer 122 is 300 nm. nm, the third Al component content in the third layer 122 is 55%, the doping concentration of Si is 1E19, the thickness of the fourth layer 121 is 800nm, the fourth Al component content in the fourth layer 121 is 65%, and the doping concentration of Si is 4E19. The energy bands of each layer of the n-type semiconductor layer 120 and the flow rate of SiH4 in this embodiment are shown in FIG. Figure 3 As shown (the energy band structure of each layer and the SiH4 flow rate in the figure represent the trend relationship between the layers), the yield of ESD is 88%.

[0036] Example 2 A UVC epitaxial structure in this embodiment is substantially the same as the structure in Embodiment 1, except that: In this embodiment, the first layer 124 of the n-type semiconductor layer 120 provides a small amount of SiH4 flow to form a small amount of Si-doped AlGaN layer. The doping concentration of Si in the first layer 124 is 3E17. The energy bands of each layer of the n-type semiconductor layer 120 and the flow of SiH4 in this embodiment are shown in FIG. Figure 4 As shown, the ESD yield is 85%.

[0037] Example 3 A UVC epitaxial structure in this embodiment is substantially the same as the structure in Embodiment 1, except that: In this embodiment, the first layer 124 of the n-type semiconductor layer 120 is an unintentionally doped u-AlGaN layer, the first Al component content in the first layer 124 is 60%, the thickness is 250nm, the thickness of the second layer 123 is 400nm, the second Al component content in the second layer 123 is 50%, the Si doping concentration is 3E19, the third Al component content of the third layer 122 is set the same as the second layer, the thickness of the fourth layer 121 is 1000nm, the fourth Al component content in the fourth layer 121 is 65%, and the Si doping concentration is 4E19. The energy bands of each layer of the n-type semiconductor layer 120 and the flow rate of SiH4 in this embodiment are shown in FIG. Figure 5 As shown (the energy band structure of each layer and the SiH4 flow rate in the figure represent the trend relationship between the layers), the yield of ESD is 80%.

[0038] Comparative Example 1 A UVC epitaxial structure in Comparative Example 1 is substantially the same as that in Example 1, except that: In Comparative Example 1, the first layer 124 of the n-type semiconductor layer 120 is an n-AlGaN layer formed by doping Si, the thickness of the first layer 124 is 250 nm, the first Al component content in the first layer 124 is 50%, and the doping concentration of Si is 8E18; the thickness of the second layer 123 is 400 nm, the second Al component content in the second layer 123 is 45%, and the doping concentration of Si is 1E19, the thickness of the third layer 122 is 300 nm, the third Al component content in the third layer 122 is 50%, and the doping concentration of Si is 3E19, the thickness of the fourth layer 121 is 800 nm, the fourth Al component content in the fourth layer 121 is 65%, and the doping concentration of Si is 4E19. The energy bands of each layer of the n-type semiconductor layer 120 in this embodiment and the flow rate of SiH4 are shown as follows. Figure 6 As shown (the energy band structure of each layer and the SiH4 flow rate in the figure represent the trend relationship between the layers). The ESD yield is 25%.

[0039] Comparative Example 2 A UVC epitaxial structure in Comparative Example 2 is substantially the same as that in Example 1, except that: In Comparative Example 2, the thickness of the first layer 124 of the n-type semiconductor layer 120 is 250 nm, the first Al component content in the first layer 124 is 50%, and it is not intentionally doped; the thickness of the second layer 123 is 400 nm, the second Al component content in the second layer 123 is 45%, and the doping concentration of Si is 1E19; the thickness of the third layer 122 is 300 nm, the third Al component content in the third layer 122 is 55%, and the doping concentration of Si is 2E19; the thickness of the fourth layer 121 is 800 nm, the fourth Al component content in the fourth layer 121 is 65%, and the doping concentration of Si is 4E19. The energy bands of each layer of the n-type semiconductor layer 120 in this embodiment and the flow rate of SiH4 are shown as follows: Figure 7 As shown (the energy band structure of each layer and the SiH4 flow rate in the figure represent the trend relationship between the layers). The ESD yield is 65%.

[0040] Comparative Example 3 A UVC epitaxial structure in Comparative Example 3 is substantially the same as that in Example 1, except that: In Comparative Example 3, the first layer 124 of the n-type semiconductor layer 120 is an n-AlGaN layer formed by doping Si, and the first Al component content in the first layer 124 is 55%, the Si doping concentration is 8E18, and the thickness is 250nm; the second Al component content in the second layer 123 is 45%, the Si doping concentration is 1E19, the thickness of the third layer 122 is 400nm, the third Al component content in the third layer 122 is 50%, the Si doping concentration is 2E19, the fourth Al component content in the fourth layer 121 is 65%, and the Si doping concentration is 5E19. The energy bands of each layer of the n-type semiconductor layer 120 in Comparative Example 3 and the flow rate of SiH4 are shown in Figure 2. Figure 8 As shown (the energy band structure of each layer and the SiH4 flow rate in the figure represent the trend relationship between the layers). The ESD yield is 40%.

[0041] Table 1 shows the yield statistics of multiple samples of the above-mentioned embodiments and comparative examples tested at 300V in the human body model. Compared with comparative examples 1-3, embodiments 1-3 show that controlling the increase of Al content and low doping (or no doping) in the first layer close to the quantum well greatly improves the ESD performance by more than 80%. When the Al component content of the first layer is controlled to be higher than the Al component content of the third layer adjacent to the electrode layer and unintentional doping is performed, the ESD yield performance is optimal, reaching 88%.

[0042] Table 1: ESD test results at 300V in human body model

[0043] The present invention optimizes the structure of the prior art, and improves the ESD performance of the UVC device by adjusting the Al component and doping concentration of the structure in the active layer adjacent to the n-type semiconductor layer and the component structure of the adjacent layer, while ensuring its excellent electrical characteristics. The adjustment method is simple to implement industrially, and not only does it not destroy the electrical characteristics and life of the original device, but also improves the overall structural performance and life of the device.

[0044] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A UVC epitaxial structure, characterized in that: include: An n-type semiconductor layer, an active layer and a p-type semiconductor layer are stacked in sequence, wherein the materials of the n-type semiconductor layer, the active layer and the p-type semiconductor layer are AlGaN-based, the n-type semiconductor layer comprises a first layer, a second layer and a third layer which are stacked in sequence along a specified direction, the first layer has a first Al component content, the second layer has a second Al component content, and the third layer has a third Al component content; the first layer contains at least a first n-type doping concentration, the second layer contains at least a second doping concentration, and the third layer contains at least a third doping concentration; the first Al component content is greater than the second Al component content and the third Al component content, the first n-type doping concentration is less than the second n-type doping concentration and the third n-type doping concentration, and the first n-type doping concentration is a low doping concentration or unintentional doping; the specified direction is the direction from the active layer to the n-type semiconductor layer.

2. The UVC epitaxial structure according to claim 1, characterized in that: The first Al component content>the third Al component content>the second Al component content.

3. The UVC epitaxial structure according to claim 1 or 2, characterized in that: The first Al component content is 55%-65%, the first n-type doping concentration is low doping or unintentional doping, the low doping concentration is 1E17-5E17, and the unintentional doping concentration is <1E17.

4. The UVC epitaxial structure according to claim 3, characterized in that: The first n-type doping concentration is less than the third n-type doping concentration and less than the second n-type doping concentration.

5. The UVC epitaxial structure according to claim 3 or 4, characterized in that: The second Al component content is 40%-55%, and the second n-type doping concentration is 2E18-5E19.

6. The UVC epitaxial structure according to claim 5, characterized in that: The third Al component content is 50%-60%, and the third n-type doping concentration is 2E18-5E19.

7. The UVC epitaxial structure according to claim 3 or 4, characterized in that: The thickness of the first layer is 80 nm-500 nm, and / or the thickness of the second layer is 80 nm-500 nm, and / or the thickness of the third layer is 400 nm-2 μm.

8. The UVC epitaxial structure according to claim 3 or 4, characterized in that: The n-type semiconductor layer also includes a fourth layer, which is stacked on the third layer along the specified direction, the fourth layer has a fourth Al component content, the fourth layer at least contains a fourth n-type doping concentration, the fourth Al component content is greater than or less than the first Al component content, and the fourth n-type doping concentration is greater than the first n-type doping concentration.

9. The UVC epitaxial structure according to claim 8, characterized in that: The fourth Al component content is greater than the first Al component content, the fourth n-type doping concentration is 2E18-5E19, and the fourth Al component content is 60%-80%.

10. A method for preparing a UVC epitaxial structure; characterized in that: include: The UVC epitaxial structure according to any one of claims 1 to 9 is formed on the buffer layer, wherein the n-type semiconductor layer is stacked on the buffer layer, and the material of the buffer layer is AlN-based.

11. A semiconductor device comprising an epitaxial structure and a first electrode and a second electrode matching the epitaxial structure, characterized in that: The epitaxial structure is the UVC epitaxial structure according to any one of claims 1 to 9.